Mechanics of materials - Craig, Roy R. , 1934- (Hoboken, New Jersey : John Wiley & Sons, 2011)
"By emphasizing the three key concepts of mechanics of solids, this new edition helps engineers improve their problem-solving skills. They?ll discover how these fundamental concepts underlie all of the applications presented, and they?ll learn how to identify the equations needed to solve various problems. New discussions are included on literature reviews, focusing on the literature review found in proposals and research articles. Groupware communication tools including blogs, wikis and meeting applications are covered. More information is also presented on transmittal letters and PowerPoint style presentations. And with the addition of detailed example problems, engineers will learn how to organize their solutions."-- Provided by publisher
1. Introduction to mechanics of materials -- 2. Stress and strain; introduction to design -- 3. Axial deformation -- 4. Torsion -- 5. Equilibrium of beams -- 6. Stresses in beams -- 7. Deflection of beams -- 8. Transformations of stress and strain; Mohr's circle -- 9. Pressure Vessels; Stresses due to combined loading -- 10.Buckling of columns -- 11.Energy methods -- 12.Special topics related to design
Keywords: SCIENCE / Mechanics / General; Strength of materials